Evaluasi Partikel Cangkang Buah Maja Sebagai Filler Pada Komposit Kampas Rem Organik - Yuda Permana, Ananto; Ula, Shofiatul; Listijorini, Erny; Saefuloh, Iman; Sudrajad, Agung; Sunardi, Sunardi (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The exploration of natural resources as materials for engineering applications is increasingly important, as organic materials offer greater environmental benefits. The Maja fruit, a typical Indonesian plant, has not been fully utilized for engineering purposes, particularly its shells. The goal of utilizing this material is to contribute to sustainable development. In this study, Maja fruit particles were used as a filler in combination with rice husk ash. The particle compositions of Maja fruit were set at 20%, 30%, and 40%, respectively. The composite fabrication process was conducted under cold conditions at a pressure of 30 MPa. The results indicated that an increase in the composition of Maja fruit shell particles led to higher compressive strength in the composite, although this caused a decrease in surface hardness. The optimal composite performance was achieved with a composition of 40% Maja fruit shell particles and 60% epoxy resin, as determined by a weighting method. It was also observed that while the inclusion of rice husk ash tended to reduce compressive strength, it contributed to enhancing the hardness of the composite.